Implementasi Pembelajaran Berdiferensiasi Untuk Meningkatkan Kemampuan Berpikir Kreatif Peserta Didik - Rezeki Noris Pane Sitorus Pane; Sorta Lumbantoruan; Sinta Dameria Simanjuntak (CV. Multi Kreasi Media, 2022)
The Implementation Of This Research Was Carried Out From May To June 2022. The Purpose Of This Study Was To Obtain Information About Student Learning Outcomes In The Form Of Creative Thinking Skills In Material 1, Namely The Relationship Between Space Diagonals, Plane Diagonals, And Diagonal Planes And Material 2 Namely The Nature Of The Spatial Structure In Class VIII Tri Sakti Catholic Middle School 2 Medan After Using The Direct Learning Model And The Differentiation Learning Model. Methods/Techniques In Collecting Data In This Research Are Tests: (1) Tests, (2) Documentation (3) Observations. To See The Improvement In Posttest Results Compared To Pretest And Posttest Results, The T-Test Using Spss Was Used For Significant Changes. The Application Of The Direct Learning Model And The Differentiation Learning Model Can Improve Student Learning Outcomes In Material 1, Namely The Relationship Between Space Diagonals, Plane Diagonals, And Diagonal Planes 2 And In Material 2, Namely The Properties Of Spatial Structures. This Can Be Seen From The Results Of The Tests Given To Students. The Results Of The Implementation Of The First Cycle By Applying The Direct Learning Method Obtained A Completeness Level Of 50% While The Implementation Of The Second Cycle By Applying The Differentiation Learning Model Obtained A Classical Completeness Level Of 67%. Then In The Results Of The T-Test, The Significance Value In The Direct Learning Model Is 0.000 And The T-Count Is 0.979 And The Differentiation Learning Model Has A Significance Value Of 0.010 And The T-Count Is 1.967. Learning Activities Carried Out By Teachers And Students Went Well With The Application Of The Differentiation Learning Model In Learning.